Utilization of Waqf Property: Analyzing an Institutional Mutawalli Challenges in Management Practices - Mutalib, Hasyeilla Abd; Maamor, Selamah (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to explore the challenges faced by the institutional mutawalli to achieve the utilisation of waqf property in their management practices. A qualitative method using purposive sampling with formal and semi-structured interview has been conducted to the representative of the institutional mutawalli. This study revealed that institutional mutawalli is facing problems with the management practices in the institution, namely personal experience in waqf area, training and development in understanding their functions, responsibilities in managing tasks associated with waqf property and waqf property management implementation. These factors are becoming a major challenge in achieving the utilisation of waqf properties in institutional mutawalli. Thus, findings from this study would contribute to the understanding of challenges in the utilisation of waqf property. Thus, it will contribute to the betterment of the waqf property for the benefit of the Ummah. Keywords: waqf property, utilisation, institutional mutawalli, qualitative JEL Classifications: A12, A13, G3, Z12